2015
DOI: 10.1039/c4cy00886c
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of PtSe2 and graphene sheets supported by TiO2 as cocatalysts synthesized via microwave techniques for improved photocatalytic activity

Abstract: Here we report a new composite material consisting of TiO 2 nanoparticles grown in the presence of a layered PtSe 2 /graphene hybrid as a high-performance photocatalytic material. The heterogeneous PtSe 2 -graphene/TiO 2 nanocomposites were successfully synthesized through a facile and fast microwaveassisted method. The prepared composites were characterized through X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) spectroscopy, transmission electron microscopy (TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…In addition to the aforementioned methods, some other approaches also have been reported to synthesize 2D PtSe 2 . For example, some pioneer works have been reported that PtSe 2 can be prepared via a Sol-Gel solution process [130][131][132][133][134]. Umar et al [135] reported the successful synthesis of scalable 2D PtSe 2 nanosheets via an aqueous-phase synthetic strategy for the first time.…”
Section: Other Methods (Molecular Beam Epitaxial Cvt)mentioning
confidence: 99%
“…In addition to the aforementioned methods, some other approaches also have been reported to synthesize 2D PtSe 2 . For example, some pioneer works have been reported that PtSe 2 can be prepared via a Sol-Gel solution process [130][131][132][133][134]. Umar et al [135] reported the successful synthesis of scalable 2D PtSe 2 nanosheets via an aqueous-phase synthetic strategy for the first time.…”
Section: Other Methods (Molecular Beam Epitaxial Cvt)mentioning
confidence: 99%
“…These polar solvents absorb microwave energy and limit localized heating and causes decomposition The advantage of microwave synthesis are, i.e., short reaction time, saving of long usage of power, extra cooled water for reflux and closed vessel to release minimum toxic gases to environment [17][18][19]. As it is already known that microwave radiation need a polar solvent for synthesis of nanomaterials.…”
Section: Growth and Characterization Of Cose 2 /Graphene-tio 2 Nanocomentioning
confidence: 99%
“…Additionally, PtSe 2 has previously been synthesized by chemical means for use in graphene hybrid materials 10 and has been theoretically predicted to be a highperformance photo-catalyst 11 . While Raman spectroscopy is used extensively for the characterization of TMDs and other nanomaterials, the Raman characteristics of PtSe 2 have not previously been reported.…”
Section: Introductionmentioning
confidence: 99%